The role of Phosphodiesterase-1 and its natural product inhibitors in Alzheimer’s disease: A review - Ahmad, Nazir; Lesa, Kaisun Nesa; Sudarmanto, Ari; Fakhrudin, Nanang; Ikawati, Zullies (Frontiers in Pharmacology, 2022)
Phosphodiesterase-1 (PDE1) is a versatile enzyme that has surprisingly received considerable attention as a possible therapeutic target in Alzheimer’s disease (AD) because it maintains the homeostasis of 3ʹ,5ʹ-cyclic adenosine monophosphate (cAMP) and 3ʹ,5ʹ-cyclic guanosine monophosphate (cGMP) in the brain. cAMP and cGMP are the two key second messengers that regulate a broad range of intracellular processes and neurocognitive functions, specifically memory and cognition, associated with AD. However, the lack of available selective drugs on the market poses challenges to identifying the beneficial effects of natural products. The present review focuses on PDE1 and its isoforms, splicing variants, location, distribution, and function; the role of PDE1 inhibitors in AD; and the use of vinpocetine and natural products as specific PDE1 inhibitors. Moreover, it aims to provide ongoing updates, identify research gaps, and present future perspectives. This review indicates the potential role of PDE1 inhibitors in the treatment of neurodegenerative disorders, such as AD. Certain clinical trials on the alleviation of AD in patients are still in progress. Among de novo outcomes, the employment of PDE1 inhibitors to treat AD is an important advancement given the absence of particular therapies in the pipeline for this highly prevalent disease. To sum up, PDE1 inhibition has been specifically proposed as a critical therapeutic approach for AD. This study provides a comprehensive review on the biological and pharmacological aspects of PDE1, its role on the Alzheimer’s diseases and its significance as AD therapeutic target in drug discovery from natural products. This review will help clinical trials and scientific research exploring new entities for the treatment and prevention of AD.